PENGEMBANGAN PEMBELAJARAN BERBASIS HOTS DALAM MENINGKATKAN KEMAMPUAN ANALISIS MATA KULIAH PEMBELAJARAN IPS SEKOLAH DASAR - Putu Ida Arsani Dewi (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
This study aims to determine whether the implementation of HOTS-based learning can improve the analysis skills of Elementary School Teacher Education students in Social Sciences Learning Subjects. This study uses an experimental study using a one group pretest-posttest research design. This type of research is a quasi experimental research with one group pretest posttest design. This study does not use a comparison class but has used a preliminary test so the effectiveness or effect of HOTS-based learning can be known with certainty. The results of this study indicate that the application of hots-based learning can improve the ability of social science learning analysis in students of elementary school teacher education at PGRI STAHN Mpu Kuturan Singaraja. metacognitive, and creative thinking which is a higher order thinking ability. HOTS-based learning or high-level thinking ability is an ability to think that not only requires the ability to remember, but also requires other higher abilities, such as the ability to think creatively and critically so that students already have these abilities can analyze a problem in a Social Sciences course . Keywords: Higher Order Thinking Skills, Social Science Learning, Elementary